(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Apiarist traditionally adopt wooden hive in beekeeping. Modern poly hive provides a superior environment to raise and keep the honeybee population more vigorous due to its high-tech internal facilities and sanitary system. This study was conducted to examine the comparative profitability and resource use efficiency of beekeeping using traditional wooden hive and modern poly hive in Bangladesh during 2017-18. A total of 60 beekeepers, all have traditional wooden hive and 15 have modern poly hive, were randomly selected from Sirajganj, Gazipur and Satkhira districts to conduct farm level survey with pre-tested questionnaire. Findings of the study reveal that per hive gross and net return were Tk. 11019.26 and 4082.45 for wooden hive and Tk. 27373.34 and 19838.42 for poly hive, respectively. Total cost of beekeeping was Tk. 6936.81 and 7534.92 per hive for wooden and poly hive, respectively. Besides, benefit-cost ratios (BCR) were 1.59 and 3.63 for wooden and poly hive, respectively. Cobb-Douglas production function analysis reveals that labour, transportation, insecticide, equipment, hive and rental costs had significant influence on the returns of beekeeping. More than two times higher BCR and significant positive dummy variable “modern poly hive” indicate the greater profitability of beekeeping in modern poly hives. Resource use efficiency analysis indicates that labour, insecticide, equipment, and honey extraction inputs were under-utilized while feed, transportation, marketing, hive, colony and rental inputs were over-utilized. Beekeeping is also affected by some constraints including high costs of modern poly hive accessories, lack of skilled labour and initial capital, inadequate transportation and marketing facilities. Government and other related organizations should take necessary measures to mitigate those problems. Based on the findings, it is recommended to adopt modern poly hive in beekeeping. Int. J. Agril. Res. Innov. Tech. 11(1): 84-91, June 2021